Role of microRNA Shuttled in Small Extracellular Vesicles Derived From Mesenchymal Stem/Stromal Cells for Osteoarticular Disease Treatment - Lara-Barba, Eliana; Araya, María Jesús; Hill, Charlotte Nicole; Bustamante-Barrientos, Felipe A.; Ortloff, Alexander; García, Cynthia; Galvez-Jiron, Felipe; Pradenas, Carolina; Luque-Campos, Noymar; Maita, Gabriela; Elizondo-Vega, Roberto; Djouad, Farida; et al. (Frontiers in Immunology, 2021)
Osteoarticular diseases (OD), such as rheumatoid arthritis (RA) and osteoarthritis (OA) are chronic autoimmune/inflammatory and age-related diseases that affect the joints and other organs for which the current therapies are not effective. Cell therapy using mesenchymal stem/stromal cells (MSCs) is an alternative treatment due to their immunomodulatory and tissue differentiation capacity. Several experimental studies in numerous diseases have demonstrated the MSCs’ therapeutic effects. However, MSCs have shown heterogeneity, instability of stemness and differentiation capacities, limited homing ability, and various adverse responses such as abnormal differentiation and tumor formation. Recently, acellular therapy based on MSC secreted factors has raised the attention of several studies. It has been shown that molecules embedded in extracellular vesicles (EVs) derived from MSCs, particularly those from the small fraction enriched in exosomes (sEVs), effectively mimic their impact in target cells. The biological effects of sEVs critically depend on their cargo, where sEVs-embedded microRNAs (miRNAs) are particularly relevant due to their crucial role in gene expression regulation. Therefore, in this review, we will focus on the effect of sEVs derived from MSCs and their miRNA cargo on target cells associated with the pathology of RA and OA and their potential therapeutic impact.